Evaluasi Elektrikal Gedung Sekolah (Studi Kasus SMP N 5 Magelang) - Muhamad risqi febrian; Sapto Nisworo; Deria Pravitasari (CV. Ulil Albab Corp, 2023)
Safe school buildings have electrical systems that prevent short circuits, overloads, and fires both of which can result from electrical short circuits at specific points. In fact, school buildings' electrical installations cannot be maintained or repaired without also requiring electrical loads. installations older than 15 years must be inspected. Electrical installations must be evaluated in accordance with the General Electrical Installation Requirements in order to resolve this issue. The findings indicated that the insulation resistance value and voltage drop remained above the PUIL; however, the voltage source decreased at 5500 VA, indicating that a more in-depth network evaluation was required. The results of inspection and testing of electrical installations show safe results, as do the selection of the type of conductor, the placement of facilities, and safety factors in accordance with PUIL standards. Some components are unsafe for use and put the user in danger. Establishment arranging likewise considers solace and security by adding electrical highlights like a public location framework, lightning bars and position of fire quenchers. The possibility of increasing activity in the future is taken into account when selecting cables and security components. For the re-planning of SMP N 5 Magelang, the RAB calculation is Rp. 452,737,848.00.